Acute Tryptophan Depletion Moja-De: A Method to Study Central Nervous Serotonin Function in Children and Adolescents - Stewart, Richard M.; Wong, Janice W. Y.; Mahfouda, Simone; Morandini, Hugo A. E.; Rao, Pradeep; Runions, Kevin C.; Zepf, Florian D. (Frontiers in Psychiatry, 2020)
Serotonin (5-HT) is widely implicated as a key neurotransmitter relevant to a range of psychiatric disorders and psychological processes. The role of central nervous 5-HT function underlying these processes can be examined through serotonergic challenge methodologies. Acute tryptophan depletion (ATD) is a key challenge method whereby a diminished dietary intake of tryptophan—the amino acid precursor to brain 5-HT synthesis—results in temporary diminished central nervous 5-HT synthesis. While this particular methodology has been used in adult populations, it was only recently that modifications were made to enable the use of ATD in child and adolescent populations. Additionally, the Moja-De modification of the ATD challenge methodology has demonstrated benefits over other ATD techniques used previously. The aim of this protocol paper is to describe the ATD Moja-De methodology in detail, its benefits, as well as studies that have been conducted to validate the procedure in child and adolescent samples. The ATD Moja-De protocol provides a potential methodology for investigating the role of central nervous 5-HT via manipulation of brain tryptophan availability in human psychopathology from a developmental viewpoint.